Research on the Use of Machine Learning on Building Facades - Günay, Ezgi; Güzelçoban Mayuk, Seher (The European Journal of Research and Development, 2022)
Artificial intelligence and its sub-branch, machine learning technologies, have developed rapidly in recent years and their use for various purposes has seemed to be increased in various sectors from automotive to medicine, from law to marketing. Similarly, these technologies have begun to be used in the building sector and in the field of architecture. These technologies are being used in many fields in architecture such as feasibility studies, building design, project control, occupational safety, earthquake resistant building design and applications, energy efficient system design, construction with smart construction equipment, smart building design, and smart facade design. Despite this increasing use in the field, it has been determined by the literature review that the number of studies focusing on the use of machine learning in architecture, especially on building facades, is low. In this sense in the study, it is aimed to examine the relationship between artificial intelligence and machine learning technologies with architecture in the context of building facades. Initially in the study the topics and the historical process related to artificial intelligence and machine learning were explained, subsequently the use of technologies on the building facades was examined through examples. In this way, a guiding resource has been created for those who want to work on this subject in the future.